Seasonal variation of air pollution and noise exposure, psychological stress and physical health among traffic police officers - Rasdi, Irniza; Syed Ismail, Sharifah Norkhadijah (2017)
Malaysian traffic police officers particularly in Kuala Lumpur spent most of their working time outdoors. Hence, they are highly susceptible to health risk resulted from vehicular-related air pollutants and noise exposure levels. Their health might fluctuate throughout the year due to seasonal variation of weather. This study explored the variation of air pollutants and noise exposure levels among 328 traffic police officers and how this variation influences their psychological and physical health. This is a repetitive cross-sectional study where data was collected in three different seasons; Dry, Wet and Inter-Seasons in Kuala Lumpur and several rural areas. Dustrak was used to measure the level of PM10. Sound Level Meter was used to measure the noise levels. Standardised Global health and global stress questionnaire were used to measure their perceived levels of stress, health, noise and air pollution. The highest level of PM10 found in urban area was recorded during the Dry Season and the lowest level was during the Wet Season. During Dry season, the PM10 level in Kuala Lumpur (0.27mg/m3) exceeded the permissible exposure level (PEL). The noise levels exceeded the PEL in all seasons for both urban and rural areas. The difference in measured PM10 and noise levels was significant between each season. The global health and stress were also significantly different across seasons. The poorest level of perceived health and stress was recorded during Wet Season. During Dry Season, higher level of stress and health were significantly correlated with higher level of noise and air pollutants. During Wet Season, higher level of stress and health were significantly correlated with lower level of noise and air pollutants. This study confirmed that level of health and stress of respondents varied across seasons and related to the level of air pollution and noise in each season.